Physical literacy: physical literacy knowledge and its relationship to physical fitness of senior high school students - Aprianisa Nur Fajrin; Soni Nopembri; Tri Ani Hastuti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction. This study aimed to investigate the level of physical literacy and its relationship with physical fitness among 10th-grade students in Sleman Regency using a correlational research design. Objective. The subjects were 64 students (32 male, 32 female) aged 15–17. The research sample using a purposive sampling technique, selected based on several criteria: non-athletes and residents of Sleman Regency. Methodology. The instrument in this study used two tests, were the Adolescence Physical Literacy Questionnaire (APLQ) and the Bleep Test. The APLQ showed good internal consistency (α = 0.951), validity (0.680–0.790), and reliability (0.837–0.981). The Bleep Test had a validity of 0.915 and reliability of 0.868.  Thus, this research instrument was valid and reliable. Data analysis used the Spearman correlation test, were carried out with the help of IBM SPSS Ver. 20. Results. The results of this study indicated that the linearity data obtained a Sig value of 0.975 > 0.05 and an F count value of 0.025 < F table of 2.528, so there was a significant linear relationship between physical literacy and physical fitness. Furthermore, hypothesis testing with Spearman analysis obtained a correlation coefficient between physical literacy and physical fitness of -0.091, these results showed a very weak relationship between the two variables. Discussion. The significance value (p-value) was 0.473 > 0.05, so it can be concluded that there is no significant relationship between physical literacy and physical fitness. Conclusions. Thus, it was concluded that there is no significant relationship between physical literacy and physical fitness among 10th-grade students in Sleman Regency.